IMPLEMENTATION OF SOCIAL STUDIES LEARNING ABOUT NATURAL DISASTER MITIGATION THROUGH BROCHURES MEDIA - Hareen, Zevy Theta Gita; Wahyudi, Agus (Konstruktivisme : Jurnal Pendidikan dan Pembelajaran, 2021)
This study aims to determine the effectiveness of the use of brochures on the ability to analyze geography based on learning outcomes in class XI Social Science Senior high school 1 Wonoayu student responses to the use of brochures in class XI Social Science Senior high school 1 Wonoayu; and identify student learning activities by using brochures in class XI Social Science Senior high school 1 Wonoayu. The variables in this study are brochure teaching materials, student responses, and student learning activities. Data collected in this study are as follows: student learning outcomes in the cognitive realm of control class increased by 33.48% where the average posttest results of 76.67 is greater than the pretest results of 57.44. Meanwhile in the experimental class, it increased by 38.79% where the 84.66 posttest results were greater than the 61.00 pretest results. When analyzing the pretest value between the control class and the experimental class, it can be seen that the average value of the control class pretest is 57.44 and the average pretest value of the experimental class is 61.00. Student responses to the brochure teaching materials were obtained based on the criteria of teaching material clarity of 83.9%, student interest 83%, attractiveness 85.2%, and student enthusiasm for learning 86.5%, and all are included in the category of Very Good. Student learning activities using brochure teaching materials in the experimental class get a percentage of 88% and conventional learning by 75%. Based on the results of data analysis, it can be concluded that the use of the Natural Disaster Mitigation brochure material in class XI Social Science Senior high school 1 Wonoayu is which effective to improve learning outcomes of class XI Social Science Senior high school 1 Wonoayu